The Loss of Masculine With Declined Serum DHT Is Associated With High Risk of Hepatocellular Carcinoma in Chinese Men - Wang, Lichun; Rasul, Azhar; Liu, Zili; Pan, Ying; Wang, Weihua; Li, Jiang; Li, Xiaomeng (Frontiers in Endocrinology, 2020)
Background: Hepatocellular carcinoma (HCC) is a male-predominant cancer. However, the relationship between dihydrotestosterone (DHT), the active form of testosterone, and HCC risk has not been established yet. Methods: We performed a serum-epidemiological study in the Chinese population. From 2010 to 2012, 106 male HCC patients and 318 age-matched controls were detected for their serum DHT and estradiol (E2). The odds ratios (ORs) and 95% confidence interval (CI) were estimated by logistic regression analysis with adjustment for potential risk factors. Bivariate Pearson correlations between hormone concentrations and liver function index were investigated. Results: Serum DHT levels were lower (to 1/3 of control）and E2 levels were higher (to 1.5 fold of control) in HCC patients. Compared with the low DHT level, men with a medium level had an adjusted multiple OR of 0.15 (95%CI 0.05-0.43, p trend < 0.01), and men with a high level had an OR of 0.05 (95%CI 0.01-0.21, p trend < 0.01). Notably, DHT concentration, but not E2, is correlated with liver injury. Conclusion: The data suggest that serum DHT is closely associated with HCC risk, providing a reference in order to accurately predict liver cancer and study the pathogenesis of this disease.